Effect of running speed on lower limb joint kinetics - Schache, A. G.; Blanch, P. D.; Dorn, T. W.; Brown, N. A. T.; Rosemond, D.; Pandy, M. G. (Medicine & Science in Sports & Exercise, 2011)
Purpose: Knowledge regarding the biomechanical function of the lower limb muscle groups across a range of running speeds is important in improving the existing understanding of human high performance as well as in aiding in the identification of factors that might be related to injury. The purpose of this study was to evaluate the effect of running speed on lower limb joint kinetics.